E. E. Cummings - Mozetič, Uroš (ELOPE (Ljubljana), 2006)
The paper presents the unique oeuvre of E.E. Cummings, who claims an outstanding position in the heritage of American poetry, as a case of Bildungsdichtung. This status is largely due to his highly innovative and iconoclastic approach to poetic composition, starting from his early rebellious endeavours drawing on an astounding variety of non-standard and downright shocking potentialities of the English language (including such peculiar linguistic and stylistic idiosyncracies as drastic changes of the syntactic English word order, shifts at the morphology and word-formation level, unorthodox use of punctuation, extravagant typography and spacing or arrangement of space between the lines, a diversity of meters and rhymes, as well as seemingly eccentric imagery), to his later and invariably maturer poetic diction - the diction of one who has apparently come to terms with the world and his fellow-beings, realising that genuine wisdom resides in the understanding and forgiveness of the inherently fallible human nature rather than in its continuous sardonic scrutiny.
Keywords: ameriška književnost; ameriška poezija; epifanija